Género, masculinidades e interseccionalidades en el Pacífico sur colombiano: aprendizajes para comprender relaciones socioambientales - Pazos, Mateo; Howland, Fanny Cecile (2025)
This Learning Note synthesizes reflections on gender, masculinities, and intersectionality in Colombia’s southern Pacific region, highlighting how identities, local knowledge, and environmental practices intersect within contexts of inequality and socio-environmental violence. It underscores the importance of situated qualitative approaches to understand territories, community relations, and conservation processes.